PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA MATERI PENYAJIAN DATA - Nabila Rahmania Az Zahra; Elly Sukmanasa; Fitri Anjaswuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the influence of the Project Based Learning model on the learning outcomes of mathematics data presentation material. This research conducted at SDIT Al Hikmah in second semester of the 2022/2023 school year. The research method used was a two group quasi-experiment design. The subject of this study fifth grade students SDIT Al Hikmah with a total 36 students. Data collection was carried out to obtain learning outcomes or N-gain is obtained using pretest and posttest. Researchers conducted a normality test with the lilliefors test of two samples normally distributed because the values of two samples were smaller than Ltabel. In the Project Based Learning class group, Lcount ≤ Ltable values are 0.024 ≤ 0.200, in the control class group the Lcalculate ≤ Ltable values are 0.072 ≤ 0.200. the homogeneity test the data is homogeneous because it is smaller than Ftable, the values are 1.006 ≤ 2.27. Furthermore, in the hypothesis test, tcount of 25.89 is greater than the ttable 2.03224, indicating that H0 is rejected and Ha is accepted. Thus, there is an influence of the Project Based Learning model on mathematics learning outcomes of data presentation material in class V SDIT Al Hikmah.